Psychometric Properties of the Diener Satisfaction With Life Scale With Five Response Options Applied to the Colombian Population - Espejo, Begoña; Martín-Carbonell, Marta; Checa, Irene; Paternina, Yadid; Fernández-Daza, Martha; Higuita, Juan D.; Albarracín, Angela; Cerquera, Ara (Frontiers in Public Health, 2022)
Introduction: The Satisfaction with Life Scale (SWLS), developed by Diener, Emmons, Larsen, and Griffin in 1985, comprises five items with seven response options in terms of agreement–disagreement. Recently, there has been a suggestion to reduce the response options of the SWLS to optimize its applicability in different cultural contexts. Objective: The study aims to assess the psychometric properties of the SWLS with five response options in the Colombian population. Specifically, we studied the dimensionality, invariance by gender and age (among a group of adolescents and emerging adults under 25 years and a group of adults of intermediate age and established adulthood under 59 years), convergent validity (with optimism), and divergent (with pessimism) and concurrent validity with other measures of well-being (flourishing, positive, and negative affects). Methodology: This project was a cross-sectional study using a non-probabilistic sample of the general population. Participants were included if they identified themselves as Colombian and were at least 18 years of age. The final sample comprised 1,255 participants. The average age was 25.62 years (SD = 8.60) ranging from 18 to 67 years of age, and 35.8% of the participants were men. In addition to SWLS, we used the Flourishing Scale (FS), Life Orientation Test-Revised (LOT-R), and Scale of Positive and Negative Experience (SPANE). Results: Cronbach's alpha coefficient (0.842), composite reliability (0.851), and average variance extracted (0.537) showed very good values. CFA was conducted to test the one-dimensional structure of FS, showing excellent goodness of fit [χ(5)2 = 15.774, p < 0.001, CFI = 0.992, TLI = 0.985, RMSEA = 0.042, 90% RMSEA CI (0.020, 0.066), and SRMR = 0.016]. The correlations calculated among life satisfaction (SWLS) with flourishing (FS), positive and negative affects (SPANE), optimism, and pessimism (LOT-R) were statistically significant and as expected. Configural, metric, and scalar invariance across gender and age were confirmed. Percentiles were provided for the total score and for age. Conclusions: The SWLS with five response options has adequate psychometric properties in the Colombian population, and the use of this version (with 5 response options) is recommended due to its greater applicability.